The Elusive P2X7 Macropore - Di Virgilio, Francesco; Schmalzing, Günther; Markwardt, Fritz (Trends in cell biology, 2018)
ATP, which is released under pathological conditions and is considered a damage-associated molecular pattern (DAMP), activates P2X7 receptors (P2X7Rs), trimeric plasma membrane ion channels selective for small cations. P2X7Rs are partners in NOD-like receptor containing a pyrin (NLRP3) inflammasome activation and promoters of tumor cell growth. P2X7R overstimulation triggers the ATP-dependent opening of a nonselective plasma membrane pore, known as a ‘macropore’, which allows fluxes of large hydrophilic molecules. The pathophysiological functions of P2X7R are thought to be dependent on activation of this conductance pathway, yet its molecular identity is unknown. Recent reports show that P2X7R permeability to organic solutes is an early and intrinsic property of the channel itself. A better understanding of P2X7R-dependent changes in plasma membrane permeability will allow a rationale development of novel anti-inflammatory and anticancer drugs. Extracellular ATP causes reversible permeabilization of mammalian cell plasma membranes due to P2X7R-dependent formation of a large conductance pore (the ‘macropore’). ATP is a major constituent of the inflammatory microenvironment and P2X7R has a key role in inflammation and immunity. Most P2X7R-stimulated immune responses depend on the activation of this permeability pathway, but the underlying mechanism is unknown. Recent electrophysiological and cell biological investigations now converge on a unified mechanistic explanation and provide hints as to the biochemical basis for the endogenous modulation of this pathway. It is anticipated that this new knowledge will have great impact on the design of novel anti-inflammatory drugs.